Mīmāṁsā Darśana dan Pengaruhnya terhadap Ajaran Agama Hindu di Bali - I Made Surada (Sanjiwani: Jurnal Filsafat, 2021)
Darśana is not just speculation or conjecture, but it has a very sublime, noble, distinctive and systematic value based on mystical spiritual experience. Nava darśana which are the Nine Hindu philosophical systems, are the nine means of correct teaching or the nine ways of proof of truth.One of the Nava Darśana, namely Mīmāṁsā. Mīmāṁsā greatly influenced the teachings of Hinduism in Bali. Mīmāṁsā teaches the way to attain deliverance (mokṣa) is to perform yajña as taught in the Vedas. In the endeavor to attain release it cannot be achieved in one birth, but must be achieved gradually, step by step, through several births. Every time a person performs a yajña, he will get a reward in the form of apūrwa, which is a force or energy that is not visible in the soul of the person who performs the yajña. With frequent yajña, the apūrva attains a certain cumulative level, which can lead the soul to deliverance.